2021
DOI: 10.3390/ijms222112049
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Inflammatory Effect of Hydrogen Gas Inhalation and Its Influence on Laser-Induced Choroidal Neovascularization in a Mouse Model of Neovascular Age-Related Macular Degeneration

Abstract: Background: Age-related macular degeneration (AMD) is a leading cause of blindness in the elderly. Choroidal neovascularization (CNV) is the major pathologic feature of neovascular AMD. Oxidative damages and the ensuing chronic inflammation are representative of trigger events. Hydrogen gas (H2) has been demonstrated as an antioxidant and plays a role in the regulation of oxidative stress and inflammation. This experiment aimed to investigate the influence of H2 inhalation on a mouse model of CNV. Methods: Las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However, the laser can damage the surrounding retinal tissue and cause persistent discomfort. Frequently required repeated intravitreal injections increase the risk of endophthalmitis and retinal detachment [ 9 ]. The eye consists of an anterior segment and a posterior segment.…”
Section: Retinopathymentioning
confidence: 99%
“…However, the laser can damage the surrounding retinal tissue and cause persistent discomfort. Frequently required repeated intravitreal injections increase the risk of endophthalmitis and retinal detachment [ 9 ]. The eye consists of an anterior segment and a posterior segment.…”
Section: Retinopathymentioning
confidence: 99%
“…Although angiogenesis and inflammation may appear to be two distinct processes, they are actually tightly related, particularly when angiogenesis occurs in adult organisms and is frequently accompanied by inflammation [ 71 ]. Recent studies suggest that several anti-inflammatory approaches such as Resveratrol/Metformi [ 72 ], Lycopene [ 73 ], cerium oxide nanoparticles [ 44 ], hydrogen gas [ 74 ], Shikonin [ 75 ], fursultiamine [ 76 ], Andrographolide [ 77 ], 5′-glucuronyl azidothymidine [ 78 ], and Pirfenidone [ 79 ], among others, can reduce laser-induced CNV formation in mice in a proof-of-principle method.…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrated that H2 reduced oxidants of the detrimental ROS, thus protecting against oxidant-induced cell injury. Hydrogen gas inhalation has been reported to decrease the levels of inflammatory cytokines including TNF-α, IL-1β, IL-6, and hypoxia-inducible factor 1 alpha ( 17 ), which were found to be elevated in KD and even higher in KD with CAL formation. Long et al reported that hydrogen gas had protective effects in a rat model of branch retinal vein occlusion via decreasing Vascular endothelial growth factor (VEGF)-α expression ( 18 ).…”
Section: Discussion and Reviewmentioning
confidence: 99%